A study of self-concept in reading in a second or foreign language in an academic context. (April 2015) - Walker, Carolyn
Abstract: This longitudinal, mixed methods study focused on the nature of, and changes in, second or foreign language (L2) reading self-concepts among international students studying on a pre-master's course. The study builds on previous research in the area of reading self-concept, but views the self as a frame for the discourse of reflexive self-beliefs. A framework was developed which showed how L2 reading self-perceptions can be linked in important ways to personal histories, motivational processes and the situational context. The findings included insights into how self-concepts of reading differed according to competence perceptions and levels of English language ability, as well as an analysis of the ways in which these self-views changed over the duration of the course. It is hoped that the study will provide insights into how students in international education situations experience learning to read and learning through reading simultaneously so that educators can support them more effectively.